PERANAN FINANCIAL TECHNOLOGY DALAM PERKEMBANGAN UMKM DI ERA PEMULIHAN EKONOMI PASCA PANDEMI COVID-19 DI INDONESIA - Rizky Azlina Siregar; Raina Linda Sari; Dede Ruslan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Technological developments have a positive impact on economic development, FinTech is an alternative to access financial services in a practical, efficient, convenient and economical way. Fintech has been recognized as an accelerator of economic growth during the national economic recovery through digital technology in the fintech lending program which can reach access to financing for the public. trillion to 92.4 million loan recipients. In order to support the development of MSMEs, fintech provides an easy and practical facility for borrowing capital online and there are not many complementary documents such as banking, so that there is a significant increase in MSMEs during the current economic recovery era. In this study using descriptive qualitative research methods derived from reading sources, articles and related secondary data. The results of this study indicate that the Fintech Industry has a positive and significant impact on Small and Medium Enterprises (MSMEs) and also increases financial inclusion, because the internet network is extensive and can reach almost all regions, in fact it makes it easier for people to gain access to various institutions, products and financial services according to their needs and abilities as well.